KARAKTERISTIK SENSORI DAN FISIKO-KIMIA MIE BASAH DENGAN SUBSTITUSI DAGING IKAN CENDRO (Tylosurus crocodilus) - Rahayu, Astri; Asnani, Asnani; Asyik, Nur (Universitas Halu Oleo, 2020)
Characteristics of Sensory and Physico-Chemistry of Wet Noodles with Substitution of Needle Fish Meat (Tylosurus crocodilus) ABSTRACT The aims of this study were to determine the effect of substitution of needlefish meat on sensory properties (color, aroma, taste and texture physical properties (water absorption, and developmental power) and chemical properties (moisture content and protein content) in wet noodle This study used Completely Randomized Design (CRD) consisting of 4 treatments, namely M0 (Wheat flour 100%), M1 (Wheat flour 95%: Needlefish meat 5%), M2 (Wheat flour 90%: Needlefish meat 10%), M3 (Wheat flour 85%: Needlefish meat 15%) that repeated for three times. Observed data were analyzed using ANOVA (Analysis of variance) at the 95% confidence level, (P> 0.05) and testing was carried out by the DMRT (Duncan Multiple Range Test) tests. The results obtained showed that substitution of Needlefish meat on wet noodles had a very significant effect on sensory values, physical properties and chemical values of wet noodles. the best treatment sensory test was obtained in treatment M1 with a fairly good panelist assessment. The mean sensory color, aroma, taste, and texture with categories (likes). The physical properties of wet noodles absorption were highest in treatment M0 (control) with a value of (60%), the development of wet noodles was highest in treatment M0 (control) with a value of 95%. The chemical analysis of the highest moisture content in the M0 treatment (control) with a moisture content of (64.06%) and the highest protein content in the M3 treatment was (12.29%). Keywords: wet noodles, needlefish meat, sensory test, physical test, chemical testABSTRAKTujuan penelitian ini adalah untuk mengetahui pengaruh substitusi daging ikan cendro terhadap sifat sensori (warna, aroma, rasa, dan tekstur) sifat fisik (daya serap air, dan daya pengembangan) serta sifat kimia (kadar air dan kadar protein) pada mie basah. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) yang terdiri dari 4 perlakuan yaitu M0 (Tepung terigu 100%), M1(Tepung terigu 95% : daging ikan cendro 5%), M2 (Tepung terigu 90% : daging ikan cendro 10%), M3 (Tepung terigu 85% : daging ikan cendro 15%). dan diulang sebanyak tiga kali. Data hasil pengamatan dianalisis menggunakan ANOVA (Analysis of variance) pada taraf kepercayaan 95%, (P>0,05) dan uji lanjut dengan DMRT (Duncan Multiple Range Test). Hasil penelitian yang diperoleh menunjukkan bahwa substitusi daging ikan cendro terhadap mie basah memberikan pengaruh nyata terhadap nilai sensori, sifat fisik dan nilai kimia mie basah. Perlakuan terbaik uji sensori yang meliputi warna, aroma, rasa, dan tekstur diperoleh pada perlakuan M1 (Tepung terigu 95% : daging ikan cendro 5%), penilaian panelis yang cukup baik, dengan kategori (suka). Sifat fisik daya serap air mie basah tertinggi pada perlakuan M0 (Tepung terigu 100%) dengan nilai sebesar (60%), daya kembang mie basah tertinggi pada perlakuan M0 (kontrol) dengan nilai sebesar 95%. Analisis kimia kadar air tertinggi pada perlakuan M0 (kontrol) dengan nilai kadar air sebesar (64,06%) dan kadar protein tertinggi pada perlakuan M3 (Tepung terigu 85% : daging ikan cendro15%) sebesar (12,29%).Kata kunci: analisis kimia, analisis sensori, analisis sifat fisik, mie basah, daging ikan cendro,